The USE OF BALINESE FABLE STORYTELLING TO IMPROVE STUDENTS’ SPEAKING SKILL OF EIGHT GRADE STUDENTS OF SMPN 3 SUKAWATI IN ACADEMIC YEAR 2019/2020 - Dharmayanti , Putu Ayu Paramita; Gyani, Kadek Putri; -Astawa , I Nengah; Wardana, I Ketut (SPHOTA: Jurnal Linguistik dan Sastra, 2022)
Speaking is an important skill because it is assumed that it is how speakers deliver thoughts and feeling. The results of the pre-test showed that most of the students in VIII H of SMPN 3 Sukawati in academic year 2019/2020 faced problem in speaking. In addition, they had difficulty in grammar, pronunciation, fluency, vocabulary and comprehension. Moreover, the objective of this study was to know whether or not speaking skill of the eighth grade students of SMPN 3 Sukawati in academic year 2019/2020 can be improved through Balinese fable storytelling. Thus, to achieve the objective of the study, the researcher conducted a class room action research. The research was done in two cycles and each cycle consisted of two sessions. The research instruments were given in order to collect the data needed. The data were analyzed by comparing the results of the pre-test and post-test which showed there were significant improvements of the subjects’ mean score from the pre-test to post-test. As supporting data, the questionnaire was also administered at the end of the last cycle and the results showed the students’ positive responses on the implementations of Balinese fable storytelling to improve speaking skill. Based on the results of pre-test, post-test and questionnaire, it could be concluded that speaking skill of the eighth grade students of SMPN 3 Sukawati in academic year 2019/2020 can be improved through Balinese fable storytelling.